USE OF ANIMATION IN TEACHING PHYSIOLOGY - Ajay Meshram, Komal; Wasudeo Meshram, Ajay; Rawekar, Alka (International Journal of Clinical and Biomedical Research, 2017)
Objectives: To evaluate the gain in knowledge of first year MBBS students with the use of animation. Methodology: Prospective Interventional study was conducted in department of physiology. 200 first year MBBS students participated in the study. 100 students (Group-A) were taken as control group to them the topic of physiology was taught by didactic method and another 100 students (Group-B) were taken as intervention group, where the same topic was taught with Power point presentation along with animation. For each lecture preand posttest was taken. Five consecutive lectures were planned with this intervention. At the same time feedback forms were given to intervention group for purpose of analyzing the results qualitatively. After this intervention the crossover of groups were done only for the sake of getting benefit of intervention. Results: Data obtained was analyzed statistically. Pre and posttest mean were taken. Key words: Animation; Chalk and board; Overhead projector; Teaching aids; Visual impact.